Chromium chains as polydentate fluoride ligands for actinides and group IV metals. Issue 18 (16th April 2018) - Leng, Ji-Dong; Kostopoulos, Andreas K.; Isherwood, Liam H.; Ariciu, Ana-Maria; Tuna, Floriana; Vitórica-Yrezábal, Iñigo J.; Pritchard, Robin G.; Whitehead, George F. S.; Timco, Grigore A.; Mills, David P.; Winpenny, Richard E. P.
Abstract : New heterometallic rings containing Cr(iii ) and tetravalent metals are reported, including a Cr6 Th2 cage. Abstract : The reactions of Cr6 horseshoe chains {[ n Pr2 NH2 ]3 [Cr6 F11 (O2 C t Bu)10 ]}2, 1 and precursors of actinides and group IV metals led to a series of ring complexes [ n Pr2 NH2 ][Cr7 TiF6 O2 (O2 C t Bu)16 ], 2, [ n Pr2 NH2 ][Cr6 Ti2 F5 O3 (O2 C t Bu)16 ], 3, [Cr6 ThF7 (O2 C t Bu)15 (Me2 SO)], 4, [( n Pr2 NH2 )2 (Cr6 Th2 F12 (O2 C t Bu)16 )], 5 and [ n Pr2 NH2 ][Cr6 U2 O2 F8 (O2 C t Bu)16 (Me2 SO)], 6 . X-ray structure studies indicate that the Cr6 chains maintain their structures in these complexes, acting as polydentate fluoride ligands. Their static magnetic properties were measured and fitted by isotropic exchange Hamiltonian. In accordance with1, the magnetic exchanges between Cr III are antiferromagnetic, while the exchange interactions can be modified by the tetravalent metals. For compound6, ferromagnetic exchanges J Cr–U and J U–U are obtained. EPR spectra of compounds2–5 were measured at Q band and were simulated. The spectrum of2 has the same profile as Cr7 Cd and Cr7 Zn rings with a ground state S = 3/2.3, 4 and5 give similar EPR spectra with S = 0 ground states.